PERLINDUNGAN HUKUM PEMEGANG SERTIFIKAT HAKATAS TANAH TERKAIT TUMPANG TINDIH KEPEMILIKAN(Putusan No. 108 / Pdt.G. / 2018 / PN Mpw) - Advanny Marshella (2023)
This research is motivated by the obligation for land rights owners to be able to register their respective lands, in the issue of land registration this is very important according to the Basic Agrarian Law in this case land registration is an important aspect of the process a proof of ownership of land rights. The purpose of this study is to determine the legal protection system for land rights holders if they are involved in overlapping ownership of a piece of land listed in government regulation No. 24 of 1997, there are several of them in Article 19 Paragraph 2 (c), Article 23 Paragraph 2, and there is Article 32 Paragraph 2, then there is Article 38 Paragraph 2 of the Basic Agrarian Law which reads Letter of proof of rights applies to very strong evidence as well as for owners Land rights that are objects in conflict will not get a protection after obtaining a decision to revoke another or double land certificate. The research that will be used in this writing is Normative Juridical in the form of provisions of statutory regulations. The results of the research that the author can convey if we have a land certificate that has been registered for a long time at the local BPN office, will be able to be reused as evidence if at any time a land conflict occurs, the data has been stored by the local BPN office and is easy to access by various parties.